Comparative Study on New AQM Mechanisms for Congestion Control - Ramakrishna B B; Prashant Ankalkoti; Demian Antony D'Mello (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2013)
As usage of network goes increasing day by day, managing network traffic becomes a very difficult task. It is important to avoid high packet loss rates in the Internet. Congestion is the one of the major issue in the present networks. Congestion Control is one of the solutions adopted to solve the congestion issue and to control it. Numbers of queue management algorithms are proposed for congestion control and to reduce high packet loss rates. Active Queue Management (AQM) is one such mechanism which provides better control over congestion. In this paper a study is made on recent load based AQM techniques that are proposed and its merits and shortfall is presented.